A Tear Inflammatory Biomarker in Dry Eye Disease - Ni Made Inten Lestari; Evelyn Komaratih; Yuyun Rindiastuti; Cita Rosita Sigit Prakoeswa (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Dry eye disease is a chronic ocular condition and significantly impacts visual function with multifactorial origin. It is characterized by tear instability and inflammation on the ocular surface. The inflammatory response initiates by synthesis and release of cytokines, Recently, there has been increasing scientific interest using tear film biomarkers that play a role in pathophysiology of dry eye disease. The objective of this study to explain relationship of tear film biomarker in dry eye.Methods: The research design of this study used literature review. The data was collected from electronic database in PubMed, Google Scholar, and website of science and predominantly published in the last 10 years.Result: The defect on the tear film component due to oxidative stress lead to ocular surface epithelial exposure, and intracellular signaling pathways are triggered, involving an inflammatory mediator which plays a role in the pathophysiology of dry eye. Using biomarker lead to better diagnosis, drug development, and effective management for dry eye disease.Conclusion: In conclusion, TNF-a, IL-6, IL-8, IL-1 by number studies to consistently reflect disease severity and strong correlation with schirmer tear test and another test for the ocular surface in dry eye disease.